DETECTION AND ANALYSIS OF POLYMORPHISM IN THE PROMOTER REGION OF EQUINE PPARCG1A GENE - D. Polasik1; B. Rogers; A. Bobrowska-Chwat; R. Pikuła (Journal of Animal and Plant Sciences, 2017)
The protein encoded by PPARCG1a gene is a key regulator of genes involved in energy metabolism. Numerous studies indicate that PPARGC1a gene may be a good marker for athletic performance in horses. Therefore the aim of this study was to detect polymorphisms in the promoter region of PPARGC1a gene and to evaluate its presence in horses belonging to nine different breeds (n = 268) as well as in elite and non-elite Thoroughbred racehorses with known racing outcomes (n = 276). By sequencing regulatory region of equine PPARGC1a gene one novel SNP (g.100.784.525 C>G) was detected which changes transcription factors binding sites. To genotype polymorphism PCR-RFLP method was applied. Frequency of alleles and genotypes showed considerable differentiation in analyzed breeds. GG genotype was found only in Standardbred, Polish Heavy Draft horses and Purebred Arabian (0.04-0.13). The distribution of PPARGC1A genotypes was in Hardy-Weinberg equilibrium except Polish Heavy Draft horses (P≤0.05). Moreover disproportionate presence of the GC genotype in elite Thoroughbred racehorses over the CC genotype in the non-elite population (OR=1.69) was noticed. Similarly GC genotype was overrepresented in distance runners in relation to sprinters analyzing all Thoroughbreds (OR=2.00) as well as only elite horses (OR=1.31). While there are multiple genes involved in athletic performance, given the association of PPARGC1A to mitochondrial biogenesis and conversion slow-twitch type I muscle fibers, this novel SNP may explain adaption in aerobic metabolism. The relationship between genotypes and gene expression should be performed next to evaluate its functional role.
Keywords: PPARCG1agene; SNP; Thoroughbred; horses